2021
DOI: 10.2196/24014
|View full text |Cite
|
Sign up to set email alerts
|

Physician Stress During Electronic Health Record Inbox Work: In Situ Measurement With Wearable Sensors

Abstract: Background Increased work through electronic health record (EHR) messaging is frequently cited as a factor of physician burnout. However, studies to date have relied on anecdotal or self-reported measures, which limit the ability to match EHR use patterns with continuous stress patterns throughout the day. Objective The aim of this study is to collect EHR use and physiologic stress data through unobtrusive means that provide objective and continuous mea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 58 publications
0
26
0
Order By: Relevance
“…14,33 However, the use of SM can have negative potential effects on provider well-being and work-life balance. 34,35 Despite the above, secure messages are currently either not billed for or are compensated at a much lower rate compared with office or telehealth visits. 36…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,33 However, the use of SM can have negative potential effects on provider well-being and work-life balance. 34,35 Despite the above, secure messages are currently either not billed for or are compensated at a much lower rate compared with office or telehealth visits. 36…”
Section: Discussionmentioning
confidence: 99%
“…14,33 However, the use of SM can have negative potential effects on provider well-being and work-life balance. 34,35 Despite the above, secure messages are currently either not billed for or are compensated at a much lower rate compared with office or telehealth visits. 36 Regulation on reimbursement for telephone and video visits, by contrast, continues to evolve since the COVID-19 pandemic started, but in certain practice settings, these types of visits are reimbursed at a considerably lower rate than office visits.…”
Section: Discussionmentioning
confidence: 99%
“…Although a high number of studies were expected to use tangible artifacts (i.e., those that can be physically manipulated in space) to monitor stress in work environments, since they are readily available and unobtrusive, the most common sensing type found within the included studies was wearables, especially off-the-shelf wrist-worn devices [ 43 , 44 , 49 , 50 , 52 , 53 , 57 , 58 , 60 , 61 , 62 ]. These results are in line with those of Garcia–Ceja et al’s review [ 9 ], where they found stress-detection studies always employ some form of wearable sensors, as they are unobtrusive and enable researchers to easily track and identify individual subjects while offering the same sensing possibilities as external devices.…”
Section: Resultsmentioning
confidence: 99%
“…These data can be collected into a repository of patient-generated health data (PGHD). 12 Six months of smartwatch wear can produce >250,000 readings of mean HR at 1-minute intervals, 13 around 1500 hours of sleep quality recording, 14 and >180 days of physical activity monitoring. 15 Similar technology is now also being incorporated into remote patient monitoring (RPM) for the health care provider market.…”
Section: New Data Sourcesmentioning
confidence: 99%